2007
DOI: 10.1152/ajplung.00452.2006
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystisstimulates MCP-1 production by alveolar epithelial cells through a JNK-dependent mechanism

Abstract: Pneumocystis carinii is an opportunistic fungal pathogen that causes pneumonia (PCP) in immunocompromised individuals. Recent studies have demonstrated that the host's immune response is clearly responsible for the majority of the pathophysiological changes associated with PCP. P. carinii interacts closely with alveolar epithelial cells (AECs); however, the nature and pathological consequences of the epithelial response remain poorly defined. Monocyte chemotactic protein-1 (MCP-1) is involved in lung inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 54 publications
3
46
1
Order By: Relevance
“…Furthermore, their marked suppressive activities may in some situations exert beneficial effects during exuberant host inflammation, including activity in suppressing TNF-a and macrophage inflammatory protein-2 (36,37). Inflammatory responses by macrophages and epithelial cells also provide important functions in Pneumocystis host defense (67,68). However, caution must be exercised, because these agents may also suppress important DC/lymphocyte-based IL-23/IL-17 responses, which are required to clear fungal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, their marked suppressive activities may in some situations exert beneficial effects during exuberant host inflammation, including activity in suppressing TNF-a and macrophage inflammatory protein-2 (36,37). Inflammatory responses by macrophages and epithelial cells also provide important functions in Pneumocystis host defense (67,68). However, caution must be exercised, because these agents may also suppress important DC/lymphocyte-based IL-23/IL-17 responses, which are required to clear fungal infections.…”
Section: Discussionmentioning
confidence: 99%
“…For example, P. murina induces alveolar epithelial cell release of monocyte chemotactic protein 1, a proinflammatory cytokine that contributes to lung injury (28) and alters alveolar epithelial cell gene expression through an NF-B-dependent mechanism (29). Other investigators have demonstrated that the ␤-glucan isolated from the Pneumocystis carinii cell wall increases macrophage inflammatory protein 2 production by alveolar epithelial cells (14).…”
Section: Discussionmentioning
confidence: 99%
“…protein expression in human synovial cells via the extracellular signal-regulated kinase pathway (38), while Pneumocystis stimulated MCP-1 production by alveolar epithelial cells through a c-Jun NH 2 -amino terminal kinase-dependent mechanism (35). MCP-1 expression was also increased in proximal tubular cells and MCs by TGF-␤1 (19,23).…”
Section: Discussionmentioning
confidence: 99%